THE DECISION-MAKING SYSTEM OF ORGANISATIONS FROM THE PERSPECTIVE OF ENVIRONMENTAL MANAGEMENT - Svetlana Mihaila, Lucia Morosan-Danila, Veronica Grosu, Violeta Codrean (USV Annals of Economics and Public Administration)
Today, organisations are increasingly concerned about the environmental impact of their activities. They strive to achieve new environmental performances by minimising the adverse effects of industrial-type development on the environment. This research takes an exploratory approach, reviewing specialised literature on the concept of environmental management, with a focus on the decision-making system. It also includes a bibliometric analysis using platforms such as Web of Science, Scopus, Google Scholar, and Biblioshiny to support the analysis of the national and international subject studied based on several criteria. In summary, the interest in environmental protection in tandem with economic-social development is the order of the day; organisations strive to harmonise economic and ecological objectives by making the correct environmental decisions, which have minimal consequences on the surrounding nature. The true novelty of this research, however, lies in its comprehensive approach to the decision-making system in the context of environmental management, a perspective that has not been extensively explored before.